One Day Some Evil Man: Inferentiality of Expressions within Political and Legal Texts in the History of the Serbian Language - Jelena Pavlović Jovanović; Milan Todorović (Slavia Meridionalis, 2025)
This paper diachronically follows the pragmatic decontextualization of phrases in political and law texts in the Serbian language. We employ the from-function-to-form approach. We analyze phrases containing unspecified referential terms. The corpora consist of (a) charters and letters of Serbian sovereigns (medieval times); (b) Serbian Uprising correspondence (beginning of the 19th century); (c) stenographic notes (end of the 19th century). The function of the scrutinized phrases remains stable throughout the subcorpora. Violation of Grice’s maxims of quality, quantity and manner occurs when the speaker/sender wants to avoid directly naming a person or directly placing an event in a precise spatial-temporal framework. These phrases execute various pragmatic functions: (a) strategy of “saving the speaker’s face” (avoid taking the blame); (b) strategy of negative politeness – avoid casting the blame onto prominent personages (medieval times); (c) strategy of avoiding responsibility for what was said or done; (d) strategy of distancing oneself from the person who is the being talked about and marring their reputation (19th century).